(untitled) (Fiep Bulletin - online, 2011)
Every country, region, state and municipal district needs reliable information about the health of its population in order to develop the health vigilance over disease. The epidemiologic vigilance service is responsible for that information and for developing actions of Compulsory Notification Diseases (CND) control, for taking part in notification activities, investigation and chain transmission interruption, particularly on diseases with a high potential for dissemination due to their power to cause outbreaks and epidemics, and to become a population health risk. In spite of the compulsory notification characteristic of these diseases, the epidemiologic vigilance faces sub registration problems, leading to technical and operational difficulties, especially in the hospital context , such as the absence of information about compulsory notification diseases on patient’s records and the health professional’s lack of knowledge regarding the registration importance. The objective of this analytic essay is to show the influences that reflect on the nonperformance of diseases notification actions by health professionals in the hospital setting. The study was conducted using a contextual analysis approach of the professional´s practice. The results indicate that the absence of time, the indifference as to the usefulness of the Epidemiologic Vigilance System, and the cure-focused activities, are factors that influence the non adherence to hospital diseases notification.